MRI of Metronidazole-Induced Encephalopathy - Mulcahy, Hyojeong (Radiol Case Rep, 2015)
We report the magnetic resonance imaging (MRI) findings of metronidazole-induced encephalopathy in a 58-year-old man who was treated with metronidazole for hepatic encephalopathy. MRI is likely to be helpful in confirming the diagnosis of metronidazole toxicity in clinically suspected cases.